SISTEM PENDUKUNG KEPUTUSAN PEMILIHAN SISWA BERPRESTASI MENGGUNAKAN METODE SIMPLE ADDITIVE WEIGHTING (SAW) PADA SMK NEGERI 03 KOTA BENGKULU - Lindry Dwi Cahyani; Liza Yulianti; Jhoanne Fredricka (Jurnal Media Infotama, 2024)
In a school, the ranking of outstanding students is usually only chosen based on their final grades, and this is also the case at SMK 03 Bengkulu City. The selection of outstanding students at SMK 03 Bengkulu City is only based on report card scores which are ranked 1 to 5. In the selection process, there are many opportunities for making wrong decisions because the student selection process is only based on one aspect, namely the student's final grade, while the attitude and achievement scores obtained outside of school are not taken into consideration as additional criteria for determining students who are considered to be successful and get scholarship. This means that it is very likely that the selected outstanding students do not reach the desired standards which does not get the best candidates. The purpose of this research is as an alternative way for schools to determine outstanding students so that it is not only based on academic scores, and there is no cheating in selecting outstanding students. The method used in this research is Simple Additive Weighting (SAW) method. The results of this research show that SAW method can provide the best results from the criteria and weights that have been determined. From the results of calculations using the SAW method, a student named Ceci Dinda Trangilang obtained a preference value of 0.96